CHARACTERIZATION OF RESERVOIR SANDSTONES USING LOG ANALYSIS TECHNICQUE EXTENDED ELASTIC IMPEDANCE IN FIELD X - Widyasandy, Dhony; Susilo, Adi; Mu'in, Fatkhul (Jurnal Neutrino, 2017)
Extended Elastic Impedance (EEI) Analysis first introduced by Whitcombe (2002) was used for the predicting lithology review and fluid in a hydrocarbon reservoir. EEI is an application of an angle that is applied in a certain range until the zone of interest (ZoI) clarified. EEI is an interesting subject to observe and very useful to be applied on seismic attributes with its ability to predict lithology and fluid where acoustic impedance of sands and shale looks almost in the same pattern. Applying this method allows the result of the sand and shale anomalies to be seen in a different way. EEI has the ability to review the estimation of elastic parameters. In this research, It used multiple parameters which analyzed directly by using an original log from well that are a / Â ratio, pseudo gamma ray, pseudo NPHI, pseudo resistivity. The results of this study indicate that the use of angle optimization on EEI can interpret the intended zone of interest.